2006
DOI: 10.2174/138920006775541525
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Blood-Brain Barrier Studies in the Pharmaceutical Industry

Abstract: The blood-brain barrier (BBB) remains one of the greatest challenges for the discovery and development of treatments for CNS disorders, which to this day remains one of the riskiest disease areas in terms of clinical success rates. Although the BBB is currently seen predominantly as a permeability obstacle for CNS drug delivery, it is becoming increasingly clear that the BBB has many more implications for the pharmaceutical industry impacting on CNS pharmacology and pathology, CNS pharmacokinetics and pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 244 publications
(273 reference statements)
2
79
0
Order By: Relevance
“…It was also reported that it is only 2-to 6-fold larger than the apical and basal surface areas, respectively, of the choroid plexus in rats (Keep and Jones, 1990). The fitted parameter A was of the same order of magnitude as the reported value (Pardridge et al, 1981;De Lange, 2004;Reichel, 2006). The method used for estimating PS 1 barely affected the fitted parameters B, C, and D. To verify parameters B and C, scaling factors for P-gp-and Bcrp-mediated efflux, in vivo PS P-gp and PS Bcrp of flavopiridol, the brain penetration of which is limited by both P-gp and Bcrp, were calculated using the in vitro CFR transport activities of P-gp and Bcrp, and fitted parameters B and C. In vivo PS P-gp was 4.3-fold higher than PS Bcrp .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…It was also reported that it is only 2-to 6-fold larger than the apical and basal surface areas, respectively, of the choroid plexus in rats (Keep and Jones, 1990). The fitted parameter A was of the same order of magnitude as the reported value (Pardridge et al, 1981;De Lange, 2004;Reichel, 2006). The method used for estimating PS 1 barely affected the fitted parameters B, C, and D. To verify parameters B and C, scaling factors for P-gp-and Bcrp-mediated efflux, in vivo PS P-gp and PS Bcrp of flavopiridol, the brain penetration of which is limited by both P-gp and Bcrp, were calculated using the in vitro CFR transport activities of P-gp and Bcrp, and fitted parameters B and C. In vivo PS P-gp was 4.3-fold higher than PS Bcrp .…”
Section: Discussionsupporting
confidence: 64%
“…Assuming an equal passive permeability per unit surface area across the BBB and BCSFB, parameter A corresponds to the difference in the surface area for drug penetration from the blood circulation into the brain and CSF. The surface area of capillaries at the BBB is 5000-fold larger than that at the BCSFB (Pardridge et al, 1981;De Lange, 2004;Reichel, 2006). It was also reported that it is only 2-to 6-fold larger than the apical and basal surface areas, respectively, of the choroid plexus in rats (Keep and Jones, 1990).…”
Section: Discussionmentioning
confidence: 94%
“…This latter consideration is especially important for compounds like BQCA which require blood-brain barrier (BBB) permeability to reach their therapeutic target; a modified version of the Rule of Five suggests a MW < 450 Da for BBB passage. 95 The multiple points for diversification on the BQCA scaffold have since resulted in a plethora of SAR studies that have generated a wide variety of analogues, some of which display substantial improvement on the characteristics of the parent compound. It is important to note however that all subsequent BQCA analogues described here were evaluated in only one functional assay against a single orthosteric ligand concentration, equating compound potencies to the EC 50 (point of inflection) of the compound's CRC in the presence of an EC 20 of ACh at human M 1 mAChR-expressing CHO cells using FLIPR calcium mobilization assays.…”
Section: ■ M 1 Machr-selective Ligandsmentioning
confidence: 99%
“…Gabapentin is a substrate of the L-type amino acid transporter, which explains the observed active uptake into the cells (Wang and Welty 1996;Friden et al 2011) The identification and selection of drug candidates with "acceptable brain penetration" has typically been based on predefined cutoff values for K p,brain (BB or often logBB); however, these vary between groups/companies. For instance, logBB = 0.3 (K p,brain = 2) has often been used as the cutoff point for NCE penetration of the BBB (Reichel 2006). Another approach uses an arbitrary cutoff point for K p,brain of greater than unity (Kalvass et al 2007a;Padowski and Pollack 2011a).…”
Section: Combination Of In Vivo Infusion With Brain Slicementioning
confidence: 99%